1998
DOI: 10.1074/jbc.273.32.19933
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Initial Characterization of a Soluble Glycine Binding Domain of the N-Methyl-d-aspartate Receptor NR1 Subunit

Abstract: Glycine is an essential co-agonist of the excitatory N-methyl-D-aspartate (NMDA) receptor, a subtype of the ionotropic glutamate receptor family. The glycine binding site of this hetero-oligomeric ion channel protein is formed by two distinct extracellular regions, S1 and S2, of the NR1 subunit, whereas the homologous domains of the NR2 subunit mediate glutamate binding. Here, segments S1 and S2 of the NR1 polypeptide were fused via a linker peptide followed by N-and C-terminally tagging with Flag and His 6 ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
6
42
2
Order By: Relevance
“…After centrifugation at 13,000 rpm for 15 min in an Eppendorf centrifuge (Westbury, NY), apoE labeled with both YFP and CFP was detected in the supernatant by Western blotting with M2 monoclonal antibodies against the FLAG tag (Sigma) (75).…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 13,000 rpm for 15 min in an Eppendorf centrifuge (Westbury, NY), apoE labeled with both YFP and CFP was detected in the supernatant by Western blotting with M2 monoclonal antibodies against the FLAG tag (Sigma) (75).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Ivanovic et al [25] reported similar results that a polypeptide fragment containing only the S1 and the S2 regions of the NR1 subunit is able to form a glycine-binding site. In comparison with our soluble receptor, their fragment was devoid of the N-terminal LIVBP-like region preceding the S1 region and the N-terminal portion (seven residues) of the extracellular loop region between M3 and M4.…”
Section: Discussionmentioning
confidence: 80%
“…In comparison with rat brain membrane preparations, the recombinant NR1-F1 and NR1-L1 show a lower affinity for the agonists glycine and -serine but not for antagonists. The S1-S2 fusion protein did not show a high affinity for the agonists either [25]. It is reported that antagonist binding is less affected by amino acid mutagenesis in the S2 region, whereas agonist binding is affected by amino acid mutation both in S1 and S2 [14,15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8, 10, and 16) consists of a portion of the N terminus of the protein before the first transmembrane segment (M1) and a large portion of the protein between the third and fourth membrane associated segments (M3 and M4). The S1S2 domain has been modeled previously based on the relatively low homology with bacterial amino acid-binding proteins (16 -22) and can be expressed independently in bacteria (23,24) and insect cells (25,26) with an apparently native fold. From homology modeling and site-directed mutagenesis, six regions (R1-R6; Fig.…”
mentioning
confidence: 99%